2018
DOI: 10.1161/jaha.118.009444
|View full text |Cite
|
Sign up to set email alerts
|

No Differences in Levels of Circulating Progenitor Endothelial Cells or Circulating Endothelial Cells Among Patients Treated With Ticagrelor Compared With Clopidogrel During Non–ST‐Segment–Elevation Myocardial Infarction

Abstract: Background Ticagrelor use during acute coronary syndromes demonstrated a decrease in all‐cause mortality in the PLATO (Platelet Inhibition and Patient Outcomes) trial. This effect has been attributed to a non–platelet‐derived improvement in endothelial function. The aim of this study was to determine differences in the number of endothelial progenitor cells and/or circulating endothelial cells found in peripheral blood in patients treated with either ticagrelor or clopid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Several studies suggested that ticagrelor ameliorated endothelial dysfunction ( 8 11 ). In contrast, other studies demonstrated that ticagrelor conferred no additional beneficial effect on endothelial dysfunction ( 5 , 12 , 13 ).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Several studies suggested that ticagrelor ameliorated endothelial dysfunction ( 8 11 ). In contrast, other studies demonstrated that ticagrelor conferred no additional beneficial effect on endothelial dysfunction ( 5 , 12 , 13 ).…”
Section: Introductionmentioning
confidence: 79%
“…Three studies analyzed CECs with 386 participants ( 13 , 31 , 32 ). A meta-analysis based on changes in ticagrelor and control groups indicated that ticagrelor did produce any significant effects on CEC levels (WMD: −1.08; 95% CI: −8.63, −6.47) ( Table 2 and Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Life’s Simple 7 utilizes these data to categorize cardiovascular health and behaviors as poor, intermediate, or ideal based on a set of predefined criteria 6 8 . Women and men had a similar distribution of participants that had poor, intermediate, or ideal scores for Life’s Simple 7 smoking status, physical activity, healthy weight, healthy diet, and cholesterol scores.…”
Section: Resultsmentioning
confidence: 99%
“…The American Heart Association has prioritized ideal cardiovascular health for all as a strategic impact goal to decrease cardiovascular mortality and increase health equity as well as overall health and well-being 6 , 7 . Ideal cardiovascular health has been defined by a composite of modifiable health factors (blood pressure, fasting blood sugar, cholesterol levels, healthy weight) and health behaviors (diet, exercise and activity, tobacco use) 8 . The relationship between ideal cardiovascular health and cardiovascular outcomes has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the effect of peripheral blood circulation and 3 types intravascular cells and peripheral blood on AMI has become a research hotspot, [42][43][44] while their mechanism is still unclear. Therefore, it is particularly important to explore the interaction between 3 types of intravascular cells and peripheral blood for formulating therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%